2020
DOI: 10.1007/s00167-020-06175-2
|View full text |Cite
|
Sign up to set email alerts
|

The amount of displacement can determine non-operative treatment in posterior cruciate ligament avulsion fracture

Abstract: Purpose It is generally agreed that surgical treatment is warranted for acute posterior cruciate ligament (PCL) avulsion fracture with displacement. However, the amount of displacement that warrants surgical treatment has not been deined. The purpose of this study was to determine the optimal cut-of value for displacement of posterior cruciate ligament avulsion fracture in determining non-operative treatment and to compare the results of non-operative treatment in acute isolated PCL avulsion fractures with non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
0
14
0
2
Order By: Relevance
“…Posterior cruciate ligament (PCL) avulsion fracture is a special kind of PCL injury and needs to be surgically addressed when the displacement or joint instability is severe. 1 Both open and arthroscopic procedures have been reported, and similar clinical results have been obtained. 2 , 3 Regarding open procedures, the fixation is direct and simple and there is no need for the learning curve of arthroscopic surgical procedures, 4 , 5 , 6 , 7 but these procedures are invasive.…”
mentioning
confidence: 67%
“…Posterior cruciate ligament (PCL) avulsion fracture is a special kind of PCL injury and needs to be surgically addressed when the displacement or joint instability is severe. 1 Both open and arthroscopic procedures have been reported, and similar clinical results have been obtained. 2 , 3 Regarding open procedures, the fixation is direct and simple and there is no need for the learning curve of arthroscopic surgical procedures, 4 , 5 , 6 , 7 but these procedures are invasive.…”
mentioning
confidence: 67%
“…Zhao et al believed that nonsurgical treatment can be successfully used for fractures with displacement less than 5 mm (22). Yoon et al found that conservative treatment could achieve satisfactory results when the displacement of a simple PCL avulsion fracture was less than 6.7 mm (18). Although these conservative treatments have achieved good results, there are many complications in the late stages of the conservative treatment of displaced PCL tibial avulsion fractures, which are easy to lead to knee instability, severe mobility limitation, and knee degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…According to the commonly used Meyers-McKeever system, conservative therapy can yield good outcomes in individuals with Meyers-McKeever type I fractures, but type II and III fractures are typically treated surgically. Some scholars conclude that acute PCL avulsion injuries with displacements of less than 6.7 mm should be considered for nonoperative treatment [11]. Other researchers found that surgery can help restore the tension of the PCL and obtain a better prognosis than nonsurgical treatment.…”
Section: Discussionmentioning
confidence: 99%